PENGARUH METODE APLIKASI VERMIKOMPOS DAN JUMLAH TANAMAN PER POT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) PADA SISTEM HIDROGANIK - iwan ashari; Agus Sugianto; Nurhidayati Nurhidayati (AGRONISMA, 2020)
The study aimed to determine the interaction of vermicompost application methods and the number of plants in pots on the growth and yield of lettuce plants. This research was conducted in the coop of Agriculture at the Islamic University of Malang and plastic houses on the street MT. Haryono 198, Dinoyo, Lowokwaru District, Malang City with a height of approvimately 550 meters above sea level, average daily temperatures around 23 oC up to 30 oC. This research in August to December 2019. This study used a Factorial Randomized Block Design (RBD) which consists of 2 factors. The first factor is vermicompost application method consisting of two levels, that is M1 (vermicompost mixed with planting media) and M2 (vermicompost is applied in the form of liquid fertilizer. Factor 2 that is number of plants in a pot (P) which consists of 3 levels, that is P1 (number of plants 1 in a pot), P2 (number of plants 2 in a pot) and P3 (number of plants 3 in a pot) from 2 factors obtained 6 treatment combination with 3 replication and plant samples 5. The results of this study indicate that in general there is no real interaction between vermicompost application method and the number of plants in pots growth parameters. However the yield parameters show a significant effect on lettuce yield.